Ethnography, Translation of Cultures and History in V. S. Naipaul’s India Trilogy, „The Loss of El Dorado” and „A Way in the World” - Roy, Satarupa Sinha (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2019)
The genre of travel writing is not only informed by an interdisciplinary aesthetic but also involves the description of peoples and the translation/re-presentation/re-interpretation of cultures. This article provides important clues as to how ethnography can be made to function as a legitimate mode of cultural and literary criticism. In doing so, this article seeks to establish that just as the ethnographer’s systematic study of the Other entails the possibility of gaining knowledge about the self, the travel writer’s knowledge of the Other, too, can often lead to a veritable gain in consciousness. Representation of the past or of history so to speak, as well as of the present which springs from that history, form a major preoccupation in Naipaul’s travel writing. To construct the present which, as a temporal category, is fairly problematic insofar as it is ephemeral and ever-fleeting and cannot be described without referring to what was or has been, one must begin with what one believes to be an understanding of the past – of history, per se. This study demonstrates how intensely emotional encounters with pastness inform the ways in which history is developed and narrativized within the discursive field of travel writing.